IDENTIFIKASI SENYAWA METABOLIT SEKUNDER PADA TUMBUHAN BELARAN TAPAH (Merremia peltata) - Arfi Humairah; Yuniarti Yuniarti; Gusti Abdul Rahmat Thamrin (Universitas Lambung Mangkurat, 2022)
Belaran Tapah (Merremia peltata) is a plant used by the community around the Special Purpose Forest Area (KHDTK) of Lambung Mangkurat University (ULM) as traditional medicine. The purpose of this study was to determine the presence of secondary metabolites in the Belaran Tapah plant with a qualitative phytochemical test which is expected to provide information about the content of secondary metabolites for the Belaran Tapah plant which is capable of being the basis for sustainable use of plants that have medicinal abilities. The sample came from KHDTK ULM, while the Wood Science Laboratory, Faculty of Forestry, ULM, was the place for testing. The method uses phytochemical screening which identifies flavonoid compounds, quinones, saponins, steroids, tannins, triterpenoids, and alkaloids with objects including roots, stems, leaves, and bark. The test results were processed into tabulated data and analyzed descriptively. Secondary metabolites indicated on stems, bark, leaves, and roots showed that the most identified compounds were saponins, almost all parts of the belaran tapah, kilayu and slapped rhino plants, except for the slapped rhino stems. Alkaloids, triterpenoids, steroids and quinones were found only in some parts of the roots, stems, leaves and bark, while flavonoids were not present in all of these plants.Belaran Tapah (Merremia peltata) merupakan tumbuhan yang digunakan masyarakat sekitar Kawasan Hutan Dengan Tujuan Khusus (KHDTK) Universitas Lambung Mangkurat (ULM) sebagai obat tradisional. Tujuannya dari penelitian ini yaitu untuk mengetahui keberadaan senyawa metabolit sekunder pada tumbuhan Belaran Tapah dengan uji fitokimia secara kualitatif yang diharapkan dapat menyajikan informasi mengenai kandungan senyawa metabolit sekunder untuk tumbuhan Belaran Tapah yang mampu sebagai dasar untuk pemanfataannya secara berkelanjutan mengenai tumbuhan yang memiliki kemampuan untuk pengobatan. Sampel berasal dari KHDTK ULM, sedangkan Laboratorium Ilmu Kayu Fakultas Kehutanan ULM sebagai tempat pengujiannya. Metodenya dengan menggunakan skrining fitokimia yang mengidentifikasi senyawa flavonoid, quinon, saponin, steroid, tanin, triterpenoid, dan alkaloid dengan objek antara lain akar, batang, daun, dan kulit. Hasil pengujian diolah ke dalam tabulasi data dan dianalisis secara deskriptif. Metabolit sekunder yang terindikasi pada batang, kulit, daun, dan akar menunjukkan bahwa yang paling banyak teridentifikasi adalah senyawa saponin, hampir semua bagian tumbuhan belaran tapah, kilayu dan tampar badak, kecuali di bagian batang tampar badak. Senyawa alkaloid, triterpenoid, steroid dan quinon ditemukan hanya di beberapa bagian akar, batang, daun dan kulit, sedangkan flavonoid tidak terdapat sama sekali dalam semua tumbuhan tersebut.